A study on the association of apolipoprotein E with oxidative stress markers, neurological function, and cognitive impairment following traumatic brain injury - Wang, Haoyang; Chen, Kun; Hou, Lijun (Frontiers in Neurology, 2025)
BackgroundTtraumatic brain injury (TBI) induces oxidative stress, which contributes to neuronal damage and cognitive impairment. Apolipoprotein E (ApoE) plays a key role in neural repair and may modulate oxidative stress responses. However, the relationship between ApoE expression at different stages after TBI and oxidative stress markers, as well as its association with cognitive outcomes, remains unclear.MethodsA total of 126 patients with TBI were prospectively enrolled and stratified according to the Glasgow Coma Scale (GCS) score on admission into mild (n = 60), moderate (n = 41), and severe groups (n = 25). Peripheral blood samples were collected at 12 h, 24 h, and 3 days after admission to measure serum levels of ApoE, glutathione (GSH), and malondialdehyde (MDA). Cognitive function was assessed prior to discharge using the Loewenstein Occupational Therapy Cognitive Assessment (LOTCA).ResultsSerum ApoE levels peaked at 24 h and slightly decreased thereafter, with overall levels increasing in proportion to TBI severity (p < 0.001). GSH levels progressively decreased, whereas MDA levels increased, with significant differences among the three groups (p < 0.001). Pre-discharge LOTCA scores were highest in the mild group and lowest in the severe group (p < 0.001). Spearman correlation analysis revealed that ApoE levels were negatively correlated with GSH (r = −0.6712) and positively correlated with MDA (r = 0.6934) and LOTCA scores (r = −0.7382) (all p < 0.0001).ConclusionApoE exhibits an injury-severity-dependent increase during the early stage of TBI, and its levels are closely associated with oxidative stress imbalance and cognitive impairment. These findings suggest that ApoE may play a critical role in both the pathological progression and neural repair following TBI.